A comparative study on tomato (Solanum lycopersicum) quality under different soil and nutrient management - KALORE, SWETA; LAD, HARDIK; NARWADE, AJAY; GARDE, YOGESH; TRIPATHI, SONAL; PATEL, KAMLESH; DUBEY, PRAMOD KUMAR; KARMAKAR, NILIMA (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during 2019–20 and 2020–21 at Navsari Agricultural University, Navsari, Gujarat to determine the quality of tomato (Solanum lycopersicum L.) cultivars in terms of their biochemical compositions grown under different soil types. Different genotypes of tomatoes (DVRT-2, GT-2, GT-6, and GT-7) were grown in normal, saline, and organic soils for two consecutive years. Different biochemical and antioxidative enzymes were analyzed from the mature fruits at the harvesting stage. The saline grown DVRT-2 cultivar revealed highest total carbohydrate content (5.97%), total antioxidant activity by DPPH (57.13 µg/ml), vitamin C (17 mg/100 gm), lycopene (16.58 mg/100 gm), antioxidant enzymes like ascorbate peroxidase (170.93 U/mg protein), catalase (9.11 U/mg protein), peroxidase (66.91 U/mg protein), superoxide dismutase (86.74 U/mg protein). Saline-grown GT-6 and DVRT-2 both had the highest phenyl alanine ammonia lyase activity (8.09 m molcinnamic ac. /g/mg). Conventional soil-grown DVRT-2, had the highest ash content (19.31%) and fat content (0.087%), total protein (0.86%). Therefore, among the cultivars, DVRT-2 was found to be a saline-resistant genotype. PCA analysis revealed a total of eight different principal components while 70% of the variance was explained by the first three PCs. In terms of nutritional content, organic soil was determined to be superior to normal soil, followed by saline cultivation. Mild stress is the cause of the qualitative enhancement in the fruits grown in organic soil.